COT-15 PATHOLOGICAL ANALYSIS OF MALIGNANT GLIOMA IN THE END STAGE. (3rd December 2022) - Hirai, Nozomi; Saito, Norihiko; Sato, Sho; Kushida, Naoki; Hiramoto, Yu; Fujita, Satoshi; Nakayama, Haruo; Hayashi, Morito; Ito, Keisuke; Sakurai, Takatoshi; Oharazeki, Toshiaki; Iwabuchi, Satoshi
Abstract: Background: Malignant gliomas have an extremely high rate of recurrence and brain invasion despite standard treatment, ultimately leading to tumor death. Tumor death is generally thought to be caused by brain herniation due to mass effect, as confirmed by studies of malignant glioma brain autopsies performed in the 1960s and 1980s. However, there have been few studies of brain autopsies of malignant gliomas after the introduction of chemotherapy with temozolomide, and the pathological characteristics of the end stage of the disease have not been clarified in recent years. In this study, we report the clinical and pathological characteristics of the end stages of malignant glioma cases treated at our hospital from the initial treatment to the confirmation of death. Methods: 10 cases of malignant glioma that were treated from initial treatment to pathological autopsy at our hospital from 2007 to 2018 were included in this study. We analyzed the pathology, neuroradiological changes, and clinical course of these cases at the end stage. Results: The mean age of the 10 patients was 59 (15-77) years, and the median overall survival was 16.5 months. The primary tumor sites were 2 frontal lobes, 3 parietal lobes, 3 temporal lobes, 1 cerebellum, and 1 multiple lesions. The direct cause of death in all cases was neurological death due to tumor progression. Gross findings of pathological autopsy specimens showed that tumor excision sites were cavitated or recurrent, but mass effect was poor and there were few cases of brain herniation. On the other hand, microscopic findings showed infiltration of tumor cells into the brain stem through the brain parenchyma. Conclusion: This study suggests that tumor invasion into the brainstem is involved as a cause of tumor death. It is possible that the new treatment may change the recurrence pattern or alter the morphology of glioma cells.